2004
DOI: 10.1109/tps.2004.826079
|View full text |Cite
|
Sign up to set email alerts
|

Waves in Magnetized Dusty Plasmas With Variable Charge on Dust Particles

Abstract: We present results obtained in recent years for wave propagation in a magnetized dusty plasma, including variable charge of the dust particles, and using a kinetic approach. Two forms of the dielectric tensor are obtained, which can be used depending on the application to be done. This dielectric tensor is used in some applications, in order to study the importance and influence of the variable charge on dust particles in the wave propagation characteristics. We first consider the magnetosonic wave and show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…The study expands previous analyses in which the case of Langmuir waves and isotropic Maxwellian distributions has been considered [9]. To our knowledge, this is one of the first instances of numerical analysis including the effect of the 'new' contribution, which usually only appears in formal analysis of wave propagation in dusty plasmas [4,15,16,[19][20][21]. For this investigation we have considered parameters which are in the range of parameters typical of stellar winds, and the results obtained have shown that the contribution of the 'new' components is very small compared to the 'conventional' contribution.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The study expands previous analyses in which the case of Langmuir waves and isotropic Maxwellian distributions has been considered [9]. To our knowledge, this is one of the first instances of numerical analysis including the effect of the 'new' contribution, which usually only appears in formal analysis of wave propagation in dusty plasmas [4,15,16,[19][20][21]. For this investigation we have considered parameters which are in the range of parameters typical of stellar winds, and the results obtained have shown that the contribution of the 'new' components is very small compared to the 'conventional' contribution.…”
Section: Discussionsupporting
confidence: 53%
“…2 we have plotted the results obtained with the dispersion relation given by Eq. (20). We have also plotted in the same figure the results obtained from a dispersion relation given by Λ C = 0, obtained by neglecting the 'new' contribution to the dielectric tensor.…”
Section: Ion-acoustic Waves Isotropic Maxwellian Distributionsmentioning
confidence: 97%
See 1 more Smart Citation
“…We have made a numerical investigation comparing the magnitudes of the 'conventional' and of the 'new' contributions to the dispersion relation, for frequencies in the range of the Langmuir waves and for frequencies in the range of the ion-sound waves. To our knowledge, it is the first instance of numerical analysis of the effect of the 'new' contribution, which has hitherto only appeared in formal analysis of wave propagation in dusty plasmas [7,10,14,[21][22][23]. For this investigation we have considered parameters which are in the range of parameters typical of stellar winds, and the results obtained have shown that the contribution of the 'new' components is very small compared to the 'conventional' contribution.…”
Section: Discussionmentioning
confidence: 99%
“…In the formulation utilized in the present paper, and in other studies available in the literature, the conventional dielectric tensor is utilized, modified by the presence of the dust. The need for the additional term, already demonstrated by theoretical analysis, [11,[17][18][19]27], has hitherto been ignored in the numerical analysis. Our results regarding the effect of this additional term are expected to appear in the near future.…”
Section: Discussionmentioning
confidence: 99%